Design and Development of Activity Management at The mosque An-Nur Dinamika University - Mochammad Afri Fitriansyah; Dewi Yani Sunarto; Norma Ningsih (Jurnal Sistem Informasi Universitas Dinamika, 2020)
An-Nur Mosque is a University of Dinamika Mosque that was established in 2002. An-Nur Mosque, Dinamika University Institute of Business and Information with a capacity of pilgrims that can accommodate as many as 300 people. UKKI stands for Islamic Spiritual Activity Unit. UKKI is an organization which serves as the mosque of An-Nur. UKKI is a unit of activity that operates on the University of Dinamika campus in the area of special religion of Islam or of course. Based on interviews and observations with takmir, one of the problems that occurred was that there was no recording of the results of the meeting so that the discussion of the meeting was not monitored the results and the discussion was repeated, Lack of publication of information so that no new students registered to take part in the SII. Lack of information dissemination through publications from various media such as posters, banners, and oral.Based on permaslahan above, the An-Nur Mosque University of Dinamika Surabaya must have a system for the process of managing An-Nur Mosque activities related to information on the schedule of activities and financial processing of the Mosque. Then the right solution is how to design and build an application that can inform the activities of An-Nur Masjid Dinamika Surabaya University activities, conduct financial processing and report making so that the manager can monitor and know the financial condition of the mosque for the evaluation of further activities.